Food-derived bio-functional peptides for the management of hyperuricemia and associated mechanism - Yanxin Wang; Mingxia Ma; Yumeng Huang; Siqing Fan; Jie Peng; Shiming Li; Xiurong Su; Yanbo Wang; Chenyang Lu (Food Science and Human Wellness)
Hyperuricemia, a metabolic disorder related to uric acid metabolism dysregulation, has become a common metabolic disease worldwide, due to changes in lifestyle and dietary structure. In recent years, owing to their high activity and few adverse effects, food-derived active peptides used as functional foods against hyperuricemia have attracted increasing attention. This article aims to focus on the challenge associated with peptide-specific preparation methods development, functional components identification, action mechanism(s) clarification, and bioavailability improvement. The current review proposed recent advances in producing the food-derived peptides with high anti-hyperuricemia activity by protein source screening and matched enzymatic hydrolysis condition adjusting, increased the knowledge about strategies to search antihyperuricemia peptides with definite structure, and emphasized the necessity of combining computer-aided approaches and activity evaluations. In addition, novel action mechanism mediated by gut microbiota was discussed, providing different insights from classical mechanism. Moreover, considering that little attention was paid previously on the structure-activity relationships of anti-hyperuricemia peptides, we collected the sequences from published studies and make a preliminary summary about the structure-activity relationships, which in turn provided guides for enzymatic hydrolysis optimization and bioavailability improvement. Hopefully, this article could promote the development, application and commercialization of food-derived anti-hyperuricemia peptides in the future.